(untitled) (Acta Polytechnica CTU Proceedings, 2022)
The Central Europe towards Sustainable Building 2022 conference was held in Prague, in July 4 - 6, 2022. The objective of the 6th International Conference Central Europe towards Sustainable Building (CESB22) was to present current activities in sustainable building with special focus on the Central European area and to bring ideas and international expertise to the region and deliver expertise from the region to enhance further development of built environment in the region as well as in a worldwide scale. The aim was to bring together engineers, researchers, academics, producers, investors, and developers to exchange and discuss their innovative approaches and ideas focused on sustainable buildings and their contribution to development of sustainable built environment in line with UN sustainable development goals. Simultaneously with CESB22, on 4 July 2022, a fourth iiSBE Forum of Young Researchers in Sustainable Building (YRSB22) took place, focusing on actual PhD research in the field of sustainable building. The conference key topics were following: • Innovative technologies and systems • New materials and components for sustainable buildings • Energy efficient buildings and districts • Adapting design, construction and operation of buildings to climatic goals • Integration of principles of circular economy into building design process • Decision-support tools and assessment methods for sustainable built environment • Retrofitting of existing building stock • Sustainable refurbishment of cultural and industrial heritage • Improving resilience of the built environment • Sustainable urban developmen Scientific comittee: Petr Hájek Jan Tywoniak Daniel Adamovský Manuela Almeida Maria Balouktsi Nina Bartošová Vlastimil Bílek Luc Boehme Rolf André Bohne Dalibor Borák Ruben Paul Borg Anatolijs Borodinecs Luis Bragança Steve Burroughs Albert De La Fuente Jan Desmyter Jakub Diviš Manish Dixit Pavol Ďurica Lukas Ferkl Ctislav Fiala Axel Föhl Kristina Fořtová Buntara Sthenly Gan Antonio García Martínez Jacopo Gaspari Vanessa Gomes Da Silva John Grunewald Matthias Haase Guillaume Habert Aylie Han Dalibor Hlaváček Alexander Hollberg Jana Hořická Giuliana Iannaccone Robert Jára Stephan Jörchel Karel Kabele Targo Kalamees Miloš Kalousek Bohumil Kasal Jiří Kolísko Pavel Kopecký Petr Kuklík Jerzy Kwiatkowski Nils Larsson Richard Lorch Antonín Lupíšek Thomas Lützkendorf Karel Maier Lenka Maierová Ricardo Mateus Tomáš Matuška Yu Morishita Andrea Moro Jan Mukařovský Jiří Nováček Jiří Novák Magdaléna Novotná Freja Nygaard Rasmussen Miles Kenneth Oglethorpe Doris Österreicher Milan Ostrý Alexander Passer Tereza Pavlů Tomas Peltan Bruno Peuportier Tomas Plauska Ronald Rovers Jan Růžička Senot Sangadji Seongwon Seo Harijanto Setiawan Renáta Schneiderová Heralová Matthew Schwarzkopf Jiri Skopek Roman Smutny Michal Sněhota Jerzy Sowa Kamil Staněk Zbyněk Svoboda Martina Sýkorová Zsuzsa Szalay Ondřej Šikula Michal Šourek Jiří Tencar Joel Ann Todd Alexandra Troi Jan Tywoniak John Van Oorschot Jure Vetršek Martin Volf Jakub Vorel Frantisek Vorlík Wei Yang Radek Zigler Ivana Žabičková Julie Železná Local organizing comittee: Alena Bílková Antonín Lupíšek Jakub Diviš Petr Hájek Petr Hejtmánek Jana Hořická Tereza Pavlů Kateřina Sojková Jan Tywoniak Martin Volf Julie Železná Guarantor of the peer review process: Petr Hájek Guarantor of the language editing: Kateřina Sojková